Korelasi Keinginan Bunuh Diri dengan Hierarki Kebutuhan Maslow dalam Film “Kembang Api” Karya Herwin Novianto - Khotima, Nurul Ashyfa; Syihabuddin, Syihabbudin (IdeBahasa, 2023)
This research aims to analyze the psychological conflicts of the four characters in the film "Kembang Api" by Herwin Novianto based on the humanistic psychology perspective of Abraham Maslow (1970). In this research, researchers used a literary psychology approach assisted by Maslow's humanistic hierarchy of needs theory by looking at the levels of physiological needs, a sense of security, a sense of love and belonging, a sense of self-esteem, and the need for self-actualization. The research method utilized is qualitative descriptive, and data is collected through observation and note-taking techniques. The findings of the research indicate that the factors leading the four characters to decide to commit suicide are the unfulfilled needs for security, love and belongingness, and self-esteem. When the characters fail to meet their needs at certain levels, it can result in stress, trauma, emotional pressure, and even lead to a desire for suicide. Based on these research results, it can be concluded that human actions are influenced by various fundamental needs. When these needs are not adequately met, the likelihood of someone deciding to end their life may increase. Conversely, if these needs are well satisfied, the probability of suicidal tendencies decreases.